Ijtihad Tidak Bisa Membatalkan Ijtihad yang Lain - Muhammad Syarif (2021)
When ijtihad has gained legitimacy, will the legal product achieved through the ijtihad process be annulled by another ijtihad, or more easily can ijtihad be "damaged" by another ijtihad. The scholars (fuqaha) agree that the ijtihad law as a result of the efforts of a judge cannot be changed with the results of other ijtihad, although in essence there is only one correct law. This is what is meant by "al-Ijtihad la yunqadl bi al-Ijtihad". Thus, the change in ijtihad referred to in this rule is a change in the results of ijtihad that occurs on the same legal object, but at different times, whether ijtihad is carried out by mujtahid, judge, qadli, or individual ijtihad as experienced by someone who changed the results of his ijtihad in determining the Qibla direction. If there is a change in ijtihad on a different object of law, such as the example experienced by a qadli, then the second ijtihad is not actually a change in ijtihad; it is just a new ijtihad unrelated to the annulment of the first ijtihad.